Interaction of smoking and occupational noise exposure on hearing loss: a cross-sectional study - Mohammadi Saber; Mehrdad Ramin; Pouryaghoub Gholamreza (BMC, 2007)
Abstract Background Noise is the most common hazardous agent at workplaces. Noise induced hearing loss (NIHL) has been known since the industrial revolution. Although NIHL is permanent, irreversible and frequent, it is preventable. The economic costs of NIHL have been estimated to be about billions of dollars. Besides, cigarette smoking is a common habit worldwide, and according to some recent studies smoking and noise may act in common causal pathways for hearing loss. Methods A cross-sectional study was designed to study the effect of smoking on NIHL in 206 male smoker workers and 206 male non-smoker workers in a large food-producing factory, in which workers were exposed to noise levels exceeding 85dBA. To determine noise exposure level, we used sound level measurements reported by industrial hygienists. A qualified audiologist assessed hearing acuity by using standardized audiometric procedures assuring at least 14 h of noise avoidance. Results We observed that the percentage of workers with hearing threshold differences of greater than or equal to 30 dB between 4000 Hz and 1000 Hz in both ears were 49.5% and 11.2% in smoker and non smoker groups, respectively (Odds ratio = 7.8, 95% CI = 4.7 - 13), and the percentage of workers with a hearing threshold of greater than 25dB at 4000 Hz in the better ear were 63.6% and 18.4% in smoker and non smoker groups, respectively. This difference was statistically significant after adjustment for age and exposure duration. Conclusion It can be concluded that smoking can accelerate noise induced hearing loss, but more research is needed to understand the underlying mechanisms. Accurate follow up of smoker workers who are exposed to noise levels exceeding 85 dBA is suggested. Smokers should periodically attend educational courses on "smoking cessation", especially in noisy workplaces.